Effect of zinc oxide nanoparticles on nitrogen removal, microbial activity and microbial community of CANON process in a membrane bioreactor. (November 2017) - Zhang, Xiaojing; Zhang, Nan; Fu, Haoqiang; Chen, Tao; Liu, Sa; Zheng, Shuhua; Zhang, Jie
Highlights: ZnO NPs performed significant effect on nitrogen removal of CANON. ZnO NPs with concentration of 1 mg L −1 showed best enhancement on CANON process. The inhibition threshold on CANON process of ZnO NPs was 10 mg L −1 . Both AOB and AAOB had self-adaption to the suppression of ZnO NPs. The long-term exposure within ZnO NPs led to biodiversity decrease of CANON. Abstract: In this study, a membrane bioreactor (MBR) was adopted for completely autotrophic nitrogen removal over nitrite (CANON) process. Zinc oxide nanoparticles (ZnO NPs) was step-wise increased to analyze the influence on nitrogen removal, microbial activity and microbial communities. Finally ZnO NPs was removed to study its recovery capability. The bioactivities of ammonia-oxidizing bacteria (AOB), anaerobic ammonia-oxidizing bacteria (AAOB) and nitrite-oxidizing bacteria (NOB) were detected by batch experiments. Results showed that the ZnO NPs with low concentration (≤5 mg L −1 ) was profitable for nitrogen removal while the high concentration performed inhibition, and it lowered the abundance of both AOB and NOB while enhanced that of AAOB. ZnO NPs with high concentration (≥10 mg L −1 ) suppressed both AOB and AAOB, and long-term exposure within ZnO NPs led to microbial diversity decrease. The inhibition threshold of ZnO NPs on CANON process was 10 mg L −1, and the profitable concentration was 1 mg L −1 .